Anesthetic management of a patient with Montgomery t-tube in-situ for direct laryngoscopy - Sukhyanti Kerai; Richa Gupta; Sonia Wadhawan; Poonam Bhadoria (Wolters Kluwer Medknow Publications, 2013)
The Montgomery silicone t-tube used for post-procedural tracheal stenosis has advantage of acting as both stent and tracheostomy tube. The anesthetic management of patient with t-tube in situ poses a challenge. Safe management of such patients requires careful planning. We describe anesthetic management for direct laryngoscopy of a patient with t-tube in situ.